The Politics of Survival - Abélès, Marc (Duke University Press, 2010)
In this provocative analysis of global politics, the anthropologist Marc Abélès argues that the meaning and aims of political action have radically changed in the era of globalization. As dangers such as terrorism and global warming have moved to the fore of global consciousness, foreboding has replaced the belief that tomorrow will be better than today. Survival, outlasting the uncertainties and threats of a precarious future, has supplanted harmonious coexistence as the primary goal of politics. Abélès contends that this political reorientation has changed our priorities and modes of political action, and generated new debates and initiatives. The proliferation of supranational and transnational organizations-from the European Union to the World Trade Organization (WTO) to Oxfam-is the visible effect of this radical transformation in our relationship to the political realm. Areas of governance as diverse as the economy, the environment, and human rights have been partially taken over by such agencies. Non-governmental organizations in particular have become linked with the mindset of risk and uncertainty; they both reflect and help produce the politics of survival.Abélès examines the new global politics, which assumes many forms and is enacted by diverse figures with varied sympathies: the officials at meetings of the WTO and the demonstrators outside them, celebrity activists, and online contributors to international charities. He makes an impassioned case that our accounts of globalization need to reckon with the preoccupations and affiliations now driving global politics. The Politics of Survival was first published in France in 2006. This English-language edition has been revised and includes a new preface
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Okt 2020)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Political psychology; Politicians -- France -- Attitudes; Public opinion -- France